Danger on the Reef - Jake Maddox (Stone Arch Books, 2020)
Jasmine Lopez and her brother Arjun love exploring the coral reefs around Fiji, where their marine biologist parents are stationed. Jasmine, already a certified scuba diver, dreams of following in her parents' footsteps and wants to help Arjun do the same. Unfortunately her younger brother is sure he already knows everything. That attitude gets them into danger when Arjun drifts too far from the group during a dive -- and straight into a reef shark.
Keywords: Sport Stories -- Sport Stories